Sistem Pakar Mendiagnosa Penyakit Kanker Menggunakan Metode Forward Chaining - Dameria Esterlina Br Jabat; Liskedame Yanti Sipayung; Megaria Purba (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
Cancer is a disease caused by abnormal growth of body tissue cells that turn into cancer cells. One of them is cervical cancer and breast cancer, this cancer often affects women. Some women tend not to know they have the disease. Data on the number of cervical cancer patients is 374 patients per year and the number of breast cancer patients is 281 per year. Knowledge and early monitoring of cervical cancer and breast cancer are needed to assist the community in carrying out early prevention and treatment. To provide a diagnosis, the help of an expert is needed, namely a specialist doctor who deals with the diagnosis and treatment of cancer. Given these conditions, it is necessary to develop a solution by designing a system that can help in overcoming the symptoms of cervical and breast cancer using an expert system for diagnosing cancer which aims to make it easier for doctors and patients to find out the symptoms of cervical cancer. and breast cancer in patients. The results showed that this expert system for diagnosing cervical cancer and breast cancer can be a medium of information, knowledge and a means of detection for cloud people in detecting the initial conditions of cervical cancer and breast cancer independently with the help of technology with this application which is expected to help in providing consultations providing information about the stage, symptoms and solutions